Incorporation of Cu/Ni in Ordered Mesoporous Co‐Based Spinels to Facilitate Oxygen Evolution and Reduction Reactions in Alkaline Media and Aprotic Li−O2 Batteries. Issue 5 (20th January 2022) - Priamushko, Tatiana; Budiyanto, Eko; Eshraghi, Nicolas; Weidenthaler, Claudia; Kahr, Jürgen; Jahn, Marcus; Tüysüz, Harun; Kleitz, Freddy
Abstract: Ordered mesoporous CuNiCo oxides were prepared via nanocasting with varied Cu/Ni ratio to establish its impact on the electrochemical performance of the catalysts. Physicochemical properties were determined along with the electrocatalytic activities toward oxygen evolution/reduction reactions (OER/ORR). Combining Cu, Ni, and Co allowed creating active and stable bifunctional electrocatalysts. CuNiCo oxide (Cu/Ni≈1 : 4) exhibited the highest current density of 411 mA cm −2 at 1.7 V vs. reversible hydrogen electrode (RHE) and required the lowest overpotential of 312 mV to reach 10 mA cm −2 in 1 m KOH after 200 cyclic voltammograms. OER measurements were also conducted in the purified 1 m KOH, where CuNiCo oxide (Cu/Ni≈1 : 4) also outperformed NiCo oxide and showed excellent chemical and catalytic stability. For ORR, Cu/Ni incorporation provided higher current density, better kinetics, and facilitated the 4e − pathway of the oxygen reduction reaction. The tests in Li−O2 cells highlighted that CuNiCo oxide can effectively promote ORR and OER at a lower overpotential. Abstract : Mix and match : Combining Cu, Ni, and Co into mesoporous mixed oxide nanocasts leads to active and stable bifunctional electrocatalysts for oxygen evolution and reduction reactions (OER and ORR). Small amount of Cu plays a substantial role in improving the catalyst conductivity and facilitating Fe−Ni interactions, which is beneficial for water oxidation. In Li−O2 cells, both charge and discharge reactions occur at lower overpotentials compared to cells with carbon cathodes, and LiOH is a main discharge product.